Exploring Proximities in Coworking Spaces: Evidence from Italy - Mariotti, Ilaria; Akhavan, Mina (European Spatial Research and Policy, 2020)
Since the mid-2000s, the rising phenomenon of coworking spaces (CSs) has provided a flexible and mainly affordable solution for freelancers, entrepreneurs, small firms and start-ups, which may had experienced the issues of isolation when working from home, to work in a shared workplace, interact, socialize and share knowledge. This article explores the phenomenon of CSs within the theoretical framework of proximity measures a là Boschma (2005) – cognitive, organisational, social and institutional – that underpin the aspects of innovation, interaction and knowledge exchange. Though some studies on CSs have indirectly studied the different aspects of proximity, only a few of them focused on the importance of proximity measures at the workspace. With the aim to fill the gap in the literature, an empirical study was applied to Italy with 549 active CSs in 2018. The data was collected through an on-line questionnaire, addressed to a sample of 326 coworkers, focusing mainly on the set of questions devoted to understanding whether coworkers have exploited the proximity typologies in their CSs, have experienced increases in their revenues and well-being. The results are critically discussed, and some insights on policy implications are proposed.